Integrated Analysis of Liver Transcriptome, miRNA, and Proteome of Chinese Indigenous Breed Ningxiang Pig in Three Developmental Stages Uncovers Significant miRNA–mRNA–Protein Networks in Lipid Metabolism - Li, Biao; Yang, Jinzeng; Gong, Yan; Xiao, Yu; Zeng, Qinghua; Xu, Kang; Duan, Yehui; He, Jianhua; He, Jun; Ma, Haiming (Frontiers in Genetics, 2021)
Liver is an important metabolic organ of mammals. During each transitional period of life, liver metabolism is programmed by a complex molecular regulatory system for multiple physiological functions, many pathways of which are regulated by hormones and cytokines, nuclear receptors, and transcription factors. To gain a comprehensive and unbiased molecular understanding of liver growth and development in Ningxiang pigs, we analyzed the mRNA, miRNA, and proteomes of the livers of Ningxiang pigs during lactation, nursery and fattening periods. A total of 22,411 genes (19,653 known mRNAs and 2,758 novel mRNAs), 1,122 miRNAs (384 known miRNAs and 738 novel miRNAs) and 1,123 unique proteins with medium and high abundance were identified by high-throughput sequencing and mass spectrometry. We show that the differences in transcriptional, post-transcriptional, or protein levels were readily identified by comparing different time periods, providing evidence that functional changes that may occur during liver development are widespread. In addition, we found many overlapping DEGs/DEMs/DGPs related to glycolipid metabolism in any group comparison. These overlapping DEGs/DEMs/DGPs may play an important role in functional transformation during liver development. Short Time-series Expression Miner (STEM) analysis revealed multiple expression patterns of mRNA, miRNA, and protein in the liver. Furthermore, several diverse key KEGG pathways , including immune defense, glycolipid metabolism, protein transport and uptake, and cell proliferation and development, were identified by combined analysis of DEGs and DGPs. A number of predicted miRNA-mRNA-protein pairs were found and validated by qRT-PCR and PRM assays. The results provide new and important information about the genetic breeding of Ningxiang pigs, which represents a foundation for further understanding the molecular regulatory mechanisms of dynamic development of liver tissue, functional transformation and lipid metabolism.